O mínimo existencial no direito tributário brasileiro: aplicação sobre as pessoas físicas e jurídica - Tognolli, Leandro Gião (2022)
The present work intends to identify the viability of defending the existential minimum in Brazilian tax law based on the analysis of the principles and rules established in the Federal Constitution of 1988. Considering that the existence of an idea of the existential minimum derives from the interpretation of certain historically established legal institutes, it was found that the Brazilian republican model adopts as its foundation the dignity of the human person and expressly establishes as fundamental objectives of the republic: the construction of a free, fair and solidary society; ensuring national development; eradicating poverty and marginalization; reduction of social and regional inequalities, as well as the promotion of the common good, without any prejudice based on origin, race, sex, color, age and any other forms of discrimination. The characteristics of the Brazilian republican principle, the fundamental rights and guarantees established in the constitutional text and the provision of rules and principles of the Federal Constitution of 1988 regarding the relationships originated from the exercise of the taxing power of the state, notably, the principle of isonomy, the principle of contributory capacity, the principle of prohibition of the tax with confiscation effect, and the possibility of enacting a complementary law to regulate the limitations on the power to tax, are norms built from constitutional provisions that allow the assessment of the existence of norms to protect the existential minimum in Brazilian tax law. In addition to the possibility of constructing norms for the protection of the existential minimum for individuals in Brazilian tax law, this study developed an analysis of their appropriateness or adequacy in the treatment given to legal entities. The study is completed by analyzing the principles and rules that conform the protection of the existential minimum in Brazilian tax law to assess the pertinence of issuing a complementary law for the creation of the taxpayer statute based on the recognition of the existential minimum as an essential core of defense of fundamental rights of taxpayers